Determining the dark matter distribution in simulated galaxies with deep learning - De Los Rios, Martín [UNESP]; Petač, Mihael; Zaldivar, Bryan; Bonaventura, Nina R; Calore, Francesca; Iocco, Fabio (Oxford University Press (OUP), 2023)
We present a novel method of inferring the dark matter (DM) content and spatial distribution within galaxies, using convolutional neural networks (CNNs) trained within state-of-the-art hydrodynamical simulations (Illustris-TNG100). Within the controlled environment of the simulation, the framework we have developed is capable of inferring the DM mass distribution within galaxies of mass ∼1011- from the gravitationally baryon-dominated internal regions to the DM-rich, baryon-depleted outskirts of the galaxies, with a mean absolute error always below ≈0.25 when using photometrical and spectroscopic information. With respect to traditional methods, the one presented here also possesses the advantages of not relying on a pre-assigned shape for the DM distribution, to be applicable to galaxies not necessarily in isolation, and to perform very well even in the absence of spectroscopic observations.
Keywords: dark matter; galaxies: General; galaxies: haloes; methods: data analysis; software: Simulations